Utilizing Machine Learning and Cloud Services to Improve Disaster Information Systems - Arief, Lathifah; Sundara, Tri (AI Society & STMIK Indonesia, 2022)
Cloud services have enabled various information system developments. In this paper, we explore the use of Amazon Sagemaker cloud services and AWS Data Exchange in disaster information systems. We proposed cloud architecture for a disaster information system and found some of the datasets provided on AWS Data Exchange could be leveraged for such system.